The role of futility judgments in improperly limiting the scope of clinical research - Harper, W. (Journal of medical ethics, 1998)
In medical research, the gathering and presenting of data can be limited in accordance with the futility judgments of the researchers. In that case, research results falling below the threshold of what the researchers deem beneficial would not to be reported in detail. As a result, the reported information would tend to be useful only to those who share the valuational assumptions of the researchers. Should this practice become entrenched, it would reduce public confidence in the medical establishment, aggravate factionalism within the research community, and unduly influence treatment decisions. I suggest alternative frameworks for measuring survival outcomes.